2011 2nd IEEE PES International Conference and Exhibition on Innovative Smart Grid Technologies 2011
DOI: 10.1109/isgteurope.2011.6162612
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of smart grid topologies using pilot installations experimental results

Abstract: In order to make smart grid feasible, the respective (a) topology and (b) control infrastructure should be determined first for the low level of the grid, i.e. microgrids or even smaller grids like a residential in-house grid, and be expandable in a larger scale. Additionally, the experimental investigation of properly designed interconnected microgrids could simulate the behavior of the whole distribution grid and thus facilitate in the transition from the traditional to the smart electric grid. Two smart gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
7
0
4
Order By: Relevance
“…SCUs are also necessary for the ac loads (or group of loads) and ac generators as shown in Fig. 1 [17], [18]. The SCUs are categorized in load SCUs (L-SCUs), generators SCUs (G-SCUs), storage SCUs (S-SCUs), and interconnection SCUs (I-SCUs), for connecting the small grid of the ac-bus to the remaining grid (SD).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…SCUs are also necessary for the ac loads (or group of loads) and ac generators as shown in Fig. 1 [17], [18]. The SCUs are categorized in load SCUs (L-SCUs), generators SCUs (G-SCUs), storage SCUs (S-SCUs), and interconnection SCUs (I-SCUs), for connecting the small grid of the ac-bus to the remaining grid (SD).…”
Section: IImentioning
confidence: 99%
“…Then, a brief description of the proposed iterative control algorithm is presented, whereas in the next section, the details are supplied on the energy storage management and the PV plants active power control strategies. Finally, the simulation results reveal that the new microgrid control strategies improve power supply reliability in grid connected and islanded situations [17] and [18].…”
Section: Introductionmentioning
confidence: 97%
“…The last module is integrated into software that runs on a microgrid-dedicated PC. This topology is implemented at the facilities of the Technological Educational Institute of Western Macedonia [1], [9], [10].…”
Section: Description Of the Microgrid Topologymentioning
confidence: 99%
“…This parameter is taken into account, since tests showed that switching on-off large loads could lead to great discharging currents, which in their turn are misleading indications for the correct estimation of the SoC by the linear method. The wrong SoC estimation can lead to unnecessary load rejection and thus decreased power supply reliability [9], [10]. Thus, the term "pseudo State of Charge" (pseudo-SoC) is defined as the SoC that is assigned to the batteries on purpose, when great discharging currents appear in a 2-minutes period and the (V mean-2 , I mean-2 ) point skips one of the above SoC areas, i.e.…”
Section: A Energy Storage Management Strategymentioning
confidence: 99%
See 1 more Smart Citation